Analysis of the Financial Performance of Savings and Loans Cooperatives in Suka Damai Cooperatives, Macang Boyfriend District in 2013-2017 West Manggarai Regency - Sri Rahayu (INVOICE : JURNAL ILMU AKUNTANSI, 2022)
The purpose of this study is how the financial performance of KSP Suka Dami in 2013 2017 by using liquidity ratios, solvency and profitability ratios based on liquidity ratios in Savings and Loans Cooperatives at Suka Damai Cooperatives, Macang Boyfriend District, the method used is descriptive method using secondary data in the form of data Financial Savings and Loan Cooperatives at the Suka Damai Cooperative, Macang girlfriend Subdistrict, the data analysis technique used is the liquidity ratio. Liquidity performance is not good based on the calculation of the 2013-2017 liquidity ratio, the value achieved is generally not good, more than 108% to 110% according to the cooperative classification. . This shows that short-term reserves and funds have developed to build cooperatives. The current ratio value in 2017 was the highest year at 110% and the lowest value at 108%. In 2016 the solvency value of KSP Suka Damai 2013-2017. in guaranteeing debt with own capital was good (between 50% and 51%), with the highest ratio in 2013 of 54% and the lowest in 2014 of 50% Profitability of KSP Suka Damai the years 2013-2017 showed a fairly good score, which was between 6%-8% but still said to be less than a good target. The highest return of equity value in 2013 was 7.84% and the lowest was in 2016 which was only 5.796%. Overall it can be said that these ratios are quite good